Cruciform position for trauma resuscitation. (25th February 2017) - Mitra, Biswadev; Fitzgerald, Mark C; Olaussen, Alexander; Thaveenthiran, Prasanthan; Bade‐Boon, Jordan; Martin, Katherine; Smit, De Villiers; Cameron, Peter A
Abstract: Multiply injured patients represent a particularly demanding subgroup of trauma patients as they require urgent simultaneous clinical assessments using physical examination, ultrasound and invasive monitoring together with critical management, including tracheal intubation, thoracostomies and central venous access. Concurrent access to multiple body regions is essential to facilitate the concept of 'horizontal' resuscitation. The current positioning of trauma patient, with arms adducted, restricts this approach. Instead, the therapeutic cruciform positioning, with arms abducted at 90°, allows planning and performing of multiple life‐saving interventions simultaneously. This positioning also provides a practical surgical field with improved sterility and procedural access.